Left Ventricular Strain Is Associated With Myocardial Recovery Following ST-Elevation Myocardial Infarction, a Prospective Longitudinal CMR Study - Taha, Mohamad B.; Jeng, Eric I.; Salerno, Michael; Moguillansky, Diego; Keeley, Ellen C.; Al-Ani, Mohammad A. (Frontiers in Cardiovascular Medicine, 2022)
Background: Infarct size following ST-elevation myocardial infarction (STEMI) is an important determinate of left ventricular (LV) dysfunction and cardiovascular morbidity and mortality. Feature tracking cardiac MRI (FT-CMR) is a technique that allows for the assessment of myocardial function via quantification of longitudinal, radial, and circumferential strain. We investigated the association between FT-CMR-derived myocardial global strain and myocardial recovery. Methods: A prospective study on patients presenting with STEMI treated with primary percutaneous coronary intervention (PCI) was conducted. CMR imaging was obtained at two interval time points, the baseline within two weeks of hospital discharge and follow-up at six months. Strain analysis was performed via FT-CMR, and recovery was quantified by the area of late gadolinium enhancement (LGE). Results: A total of n=14 patients met inclusion and exclusion criteria and were analyzed. There was a significant reduction in the infarct size, as measured by LGE mass percentage of the left ventricular muscle mass, between the initial and follow-up CMR (19.7%, IQR 12.2-23.9 vs. 17.1%, IQR 8.3-22.5, p = 0.04). Initial strain parameters were inversely correlated with the initial edema mass and the decrease in LGE mass between the initial and follow-up CMR. All LV global strains had high accuracy for the prediction of a reduction in LGE mass by 50% or more. Conclusions: LV global strains measured after primary PCI can predict the extent of myocardial recovery.